ANALYSIS OF FACTORS INFLUENCING THE SUSTAINABLE COMMERCIALIZATION OF NON-TIMBER FOREST PRODUCTS BY RURAL HOUSEHOLDS IN DELTA STATE, NIGERIA - Peter Ifeanyichukwu NWANDU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The research was on the analyses factors influencing sustainable commercialization of Non- Timber Forest Products (NTFPs) among rural households in Delta State, Nigeria. The sampling techniques used to select 340 rural households was the multistage random sampling. Data were gathered with the aid of a structured questionnaire and analysed using descriptive statistics and regression analysis. Results showed that about 66.5% men and women of active age were involved with respect to NTFPs commercialization. There were more head of households with formal education (51.8%), though they were more of First School Leaving Certificate (FSLC). The study found the mean household size of 8 persons. Commercialization of NTFPs was not sustained. Forest conservation was poor and deforestation was high (72.5%). The regression analysis with an R2value of 0.948 and F-ratio of 254.712 implied a significant impact between the dependent and independent variables at 0,05 level. The explanatory coefficients and t- values (in parenthesis) of educational qualification 0.437 (2.758), access to technology 2.695 (2.324), access to credit4.415(5.721), total household size 2.421(3.677), amount of NTFPs resources owned 2.68 (4.434) and extension services received 2.593 (3.316) were significant. Recommendations include improvement in technology used in NTFPs production. Adopting participatory approach towards NTFPs management.